The nanostructure of porous cobalt coatings deposited by magnetron sputtering in helium atmosphere. (May 2018) - Lacroix, B.; Godinho, V.; Fernández, A.
Highlights: Cobalt coatings containing He-filled nanopores are grown by magnetron sputtering. Helium density and pressure are measured in pores of different size by STEM-EELS. He density in most of the pores (40–100 at./nm 3 ) lead to pressure in the GPa range. Helium is at the equilibrium pressure and remains stable inside the pores. Abstract: In this work, (scanning) transmission electron microscopy has been used to study the nanostructure of porous cobalt coatings obtained by magnetron sputtering using helium as process gas. This nanostructure consists of closed pores of different nanometric size (about 4–20 nm) that are distributed all over a nanocrystalline Co matrix and filled with the deposition gas. Spatially resolved electron energy-loss spectroscopy analysis was applied to measure and map, with high lateral resolution, the relevant physical properties (density, pressure and He-K edge shift) of helium trapped inside these individual nanopores, in order to provide new insights about the growth mechanism involved in such systems. In particular, a coefficient of proportionality, C  = 0.039 eV nm 3, between the blue shift of the He K-edge and the He density has been found. In addition, very high He densities (10–100 at./nm 3 ) and pressures in the gigapascal range (0.05–5.0 GPa) have been measured. The linear dependence of these parameters as a function of the inverse radii obeying to the Laplace-Young law for most of the pores suggests that their formation during the coating's growth takes place in regime of elastic deformation of the Co matrix.